2003
DOI: 10.1890/02-0439
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Ecology of Predator–prey Interactions: Corridors and Patch Shape Influence Seed Predation

Abstract: Corridors that connect patches of disjunct habitat may be promising tools for mediating the negative impacts of habitat fragmentation, but little is known about how corridors affect ecological interactions. In eight 12-ha experimental landscapes, we examined how corridors affect the impact of invertebrate, rodent, and avian seed predators on pokeweed, Phytolacca americana. Over 13 months in 2000 and 2001, we quantified the effects of patch shape, connectivity, and predator type on the number of seeds germinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
69
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 64 publications
13
69
1
Order By: Relevance
“…These results also indicate that the spatial and temporal scales of hypoxic episodes determine trophic effects (Diaz & Rosenberg 1995, Eby & Crowder 2004, as observed in other consumer-prey interactions (Orrock et al 2003). Our hypoxic sites were in close proximity (100s of meters) to shallow normoxic sites, where predators congregate during hypoxia (Lenihan et al 2001.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These results also indicate that the spatial and temporal scales of hypoxic episodes determine trophic effects (Diaz & Rosenberg 1995, Eby & Crowder 2004, as observed in other consumer-prey interactions (Orrock et al 2003). Our hypoxic sites were in close proximity (100s of meters) to shallow normoxic sites, where predators congregate during hypoxia (Lenihan et al 2001.…”
Section: Discussionsupporting
confidence: 77%
“…Such species probably do not exhibit increased vulnerability during hypoxia, because behavioral changes during hypoxic conditions should not affect their primary defense (Vermeij 1987). In contrast, species such as Macoma balthica and Mya arenaria (Taylor & Eggleston 2000), which have evolved a deep burial depth in response to predators, are more likely to be more vulnerable to predators under hypoxia because they migrate to the sediment surface where they are easily detected.These results also indicate that the spatial and temporal scales of hypoxic episodes determine trophic effects (Diaz & Rosenberg 1995, Eby & Crowder 2004, as observed in other consumer-prey interactions (Orrock et al 2003). Our hypoxic sites were in close proximity (100s of meters) to shallow normoxic sites, where predators congregate during hypoxia (Lenihan et al 2001.…”
supporting
confidence: 77%
“…Once species colonize, we know from prior studies that corridors affect species interactions such as pollination (29) and seed predation (30), which may help to maintain elevated diversity in connected patches. Colonization sets an upper limit on the size of the local species pool, but it remains to be determined how much dispersal, relative to other factors, contributes to the long-term maintenance of elevated species richness.…”
Section: Resultsmentioning
confidence: 99%
“…Seed predation by insects may change the recruitment rate and the abundance of the host plant (e.g., Jules, 1998;Louda, 1982). Several studies have investigated seed predation in fragmented landscapes and have shown that it may increase with fragmentation (Orrock, Danielson, & Burns, 2003;Fleury, & Galetti, 2006;Galetti, Donatti, & Pires, 2006;Orrock, Levey, & Danielson, 2006). Similarly to plant-pollinator interactions, other studies showed the opposite pattern, where antagonistic interactions may also be disturbed by fragmentation; possibly because the abundance and diversity of antagonistic animals in small populations of plants offer fewer resources to herbivores and seed predators (Colling, & Matthies, 2004;Kéry, Matthies, & Fischer, 2001;Ehlers, & Olesen, 2003).…”
mentioning
confidence: 99%